2001
DOI: 10.1161/01.cir.103.21.2539
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous In Situ Coronary Venous Arterialization

Abstract: Abstract-Diffuse coronary artery disease is frequently untreatable by coronary artery bypass or angioplasty. Many such "no-option" patients have been subjects for trials of angiogenesis using growth factor manipulation or laser injury. We think these novel revascularization strategies are limited by insufficient inflow to putative areas of new microvasculature and thus seek a more mechanical solution. We report the use of a catheter-based system for arterializing the adjacent anterior cardiac vein in a patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…For example, Gerber et al (2001) suggest that patients with an AIA cross by GCV may not be candidates for percutaneous in situ coronary artery bypass (PICAB) because the overlap of vessels may obscure the detection of significant calcification. Oesterle et al (2001) indicate that their percutaneous in situ coronary venous arterialization (PICVA) procedure was carried out on a "parallel anterior interventricular vein" (implying a long left-side initial course). It is clear that the particular vein anatomy in individual patients influences the mechanics and outcomes of some procedures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gerber et al (2001) suggest that patients with an AIA cross by GCV may not be candidates for percutaneous in situ coronary artery bypass (PICAB) because the overlap of vessels may obscure the detection of significant calcification. Oesterle et al (2001) indicate that their percutaneous in situ coronary venous arterialization (PICVA) procedure was carried out on a "parallel anterior interventricular vein" (implying a long left-side initial course). It is clear that the particular vein anatomy in individual patients influences the mechanics and outcomes of some procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A phase 1 feasibility trial of PICVA was initiated in Germany in 1998. A description of this limited trial and a report of the first patient to have a successful PICVA is published [1]. This limited feasibility trial was designed to test the concept of PICVA and the practicality of the enabling devices for both PICVA and PICAB.…”
Section: Resultsmentioning
confidence: 99%
“…We introduced the concept of percutaneous in situ coronary artery bypass (PICAB) several years ago and suggested that it could ultimately replace bypass surgery as a less invasive approach to coronary revascularization (Fig. 1) [1]. Although this developing technology has been challenged by expected and unforeseen clinical and mechanical obstacles, we continue to believe that catheter‐based coronary bypass can become a broad‐based interventional application.…”
Section: Introductionmentioning
confidence: 99%
“…предложена операция лазерной туннелизации мио-карда, однако, несмотря на вполне обнадеживающие первые клинические результаты [12][13][14], эта операция так и не смогла стать массовой при указанном типе атеросклеротических поражений коронарных арте-рий [15,16]. Другие методы, такие как in-situ артери-ализация венозной системы сердца из-за плохого состояния дистального русла [17], сочетание хирурги-ческой реваскуляризации с генной терапией (интра-коронарное введение фактора роста эндотелиальных клеток VEGF) [18] пока находятся на стадии разра-ботки. Интервенционные методы лечения до послед-него времени считались малоэффективными.…”
Section: Discussionunclassified